2015
DOI: 10.1186/s12935-015-0204-2
|View full text |Cite
|
Sign up to set email alerts
|

Up regulation of Bax and down regulation of Bcl2 during 3-NC mediated apoptosis in human cancer cells

Abstract: BackgroundRecently, we have reported the induction of apoptosis by 2-amino-4-(3-nitrophenyl)-3-cyano-7-(dimethylamino)-4H-chromene (3-NC) in HepG2, T47D and HCT116 cells with low nano molar IC50 values. In this study, anti-proliferative effects of modified 4-aryle-4H-chromenes derivatives; 2-amino-4-(3-bromophenyl)-3-cyano-7-(dimethylamino)-4H-chromene (3-BC), 2-amino-4-(3-trifluoromethylphenyl)-3-cyano-7-(dimethylamino)-4H-chromene (3-TFC) and 2-amino-4-(4,5-methylenedioxyphenyl)-3-cyano-7-(dimethylamino)-4H-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(84 citation statements)
references
References 42 publications
7
77
0
Order By: Relevance
“…The ratio of pro-apoptotic and anti-apoptotic proteins determines the fate of the cell (An et al, 2004). Up-regulation of Bax and down-regulation of Bcl-2 is usually associated with the cell death and by using the ratio of Bax / Bcl-2 proteins, the fate of cell could be determined (Naseri et al, 2015;Gul-e-Saba et al, 2019). These findings were in parallel with previous studies performed on Vitex rotundifolia and other species of genus Vitex.…”
Section: Discussionsupporting
confidence: 81%
“…The ratio of pro-apoptotic and anti-apoptotic proteins determines the fate of the cell (An et al, 2004). Up-regulation of Bax and down-regulation of Bcl-2 is usually associated with the cell death and by using the ratio of Bax / Bcl-2 proteins, the fate of cell could be determined (Naseri et al, 2015;Gul-e-Saba et al, 2019). These findings were in parallel with previous studies performed on Vitex rotundifolia and other species of genus Vitex.…”
Section: Discussionsupporting
confidence: 81%
“…The cell death pathway may include the activation of pro-apoptotic events in the cell, which begin with the increased permeability of mitochondrial membrane caused by Bax and Bak proteins, resulting in the release of cytochrome c, eventually activating CASP9 and then CASP3. In addition, Bcl-2 and Bcl-xL proteins orientate at the surface of endoplasmic reticulum, mitochondria and nucleus, preventing the assembly of Bax and Bak proteins and hence, exhibiting anti-apoptotic activity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the expression of MCP-1 protein showed a peak, blocking the apoptotic pathway and inhibiting the occurrence of apoptosis [5,21]. However, the ratio of Bcl-2/Bax is closely related to cell apoptosis and survival [6,22]. In this study, the results showed that the number of apoptotic cells in myocardial tissues was increased gradually with prolonged time of infarction, and the expression of Bax protein was also increased gradually, indicating that cardiomyoctyte apoptosis was gradually aggravated with prolonged time of infarction.…”
Section: Discussionmentioning
confidence: 99%
“…The paraffin tissues were cut into 4 ÎŒm slices. Detection of serum IL-10 expression (ELISA) 6 The expression of IL-10 in venous blood of mice was detected by enzyme-linked immunosorbent assay (ELISA). The operations were conducted based on the kit (Andy gene) instructions.…”
Section: Preparation Of Histological Sections and Stainingmentioning
confidence: 99%
See 1 more Smart Citation